Two Patient Care Information Systems in the Same Hospital: Beyond Technical Aspects - van der Meijden, M. J.; Solen, I.; Hasman, A.; Troost, J.; Tange, H. J. (Methods of Information in Medicine, 2003)
Objectives: To compare two clinical workstations in one hospital with respect to technical, organizational, cultural and human factors. One clinical workstation was a GUI to the HIS. The other was an electronic patient record for stroke.Methods: Data were collected by means of in-depth interviews with end-users of both clinical workstations. The interviews were audio taped and transcribed for analysis.Results: End users assessed both clinical workstations as user friendly. Coordination between health care workers was perceived to be enhanced. However, in both situations poor communication between management, implementers and users resulted in uncertainty and skepticism about future perspectives. Furthermore, it appeared that inpatient and outpatient settings needed clinical workstations with different requirements for an optimal fit between work practices and information system.Conclusions: Regardless of the domain and content of a workstation, it can support coordination between disciplines. The communication concerning the information technology strategy deserves much attention. Finally, the requirements for inpatient and outpatient workstations differ.
Keywords: Computerized medical records systems; hospital information systems; evaluation studies